PELATIHAN LARI SIRKUIT 2 X 10 MENIT DAN PELATIHAN LARI KONTINYU 2 X 10 MENIT DAPAT MENINGKATKAN VO2 MAX TAEKWONDOIN PUTRA KABUPATEN MANGGARAI - NTT - Sesilia Noy, Regina; Pangkahila, Alex; Jawi, I Made (Sport and Fitness Journal, 2014)
VO2 max is very important in everyday life, so as to facilitate any physicalactivity, specially for athletes in order to achieve maximum performance. In aneffort to increase VO2 max training should be carried out regularly, measured andplanned. This study aims to determine the increase in VO2 max through circuittraining run and run continuously. The sample is taekwondoin son Manggarai-NTTwith an average age of 15 years. This study is an experimental study with the studydesign used was Randomized Pre and Post Test Group desigen. With a totalsample of 7 people in each group. Samples were randomly selected. Treatmentgroup 1 (KP1) given training run circuit 2 x 10 minute and Treatment Group 2(KP2) are given continuous training run 2 x 10 minute. Training carried out for 6weeks with a frequency of four times a week starting at 17:00 to 18:00 pm locatedat Frans Sales Lega Airport Manggarai-NTT. The analysis showed an increase inVO2 max was significantly (p <0.05) against both groups fled. In both groups thecircuit run by Pulse Oxymeter and Norma Cooper an increase in VO2 max with p<0.05, as well as a continuous run either by Pulse Oxymeter and Norma Cooperwith an increase in VO2 max value of p <0.05. The results of this analysis meansthat either the training or circuit training run run continuously to improve VO2max. Based on a comparison of test data by an independent test after training inboth groups either by Pulse Oxymeter and Norma Cooper in get p values > 0.05, orthere is no significant difference. Based on these results it can be concluded thatthe run circuit training and continuous training run together can increase VO2 maxand there was no significant difference. The results of this study are expected toincrease the knowledge of coaches, teachers and taekwondoin to perform trainingon a regular basis and are also expected to do similar research that examines VO2max with different training.
Keywords: Running circuit, Running continuous, VO2 max.